Prevention of healthcare-associated invasive aspergillosis during hospital construction/renovation works. Issue 1 (September 2019) - Talento, A.F.; Fitzgerald, M.; Redington, B.; O'Sullivan, N.; Fenelon, L.; Rogers, T.R.
Summary: The association between healthcare-associated invasive aspergillosis and hospital construction/building works is well recognized. This infection can cause significant morbidity and mortality and imposes a substantial burden on the healthcare system. The population of patients at risk for this opportunistic infection has expanded and multi-triazole drug resistance has emerged globally. Hence the need for a multi-faceted approach to prevent acquisition of invasive aspergillosis in acute care settings. This article is a summary of the Irish National Guidelines for the prevention of healthcare-associated aspergillosis which is based on published reports, international clinical guidelines, official engineering standards, and technical guidelines. We discuss the key recommendations and strategies for the prevention of invasive aspergillosis from the planning/pre-construction, construction, and post-construction phases. The importance of multi-disciplinary team involvement, education, and communication is emphasized.